Oral Health of Seniors Aged 65-74 and 75 and More Years in the Czech Republic - Z. Broukal; O. Krejsa; L. Mrklas; E. Lenčová (Czech Dental Chamber, 2006)
Nation-wide survey of oral health of seniors aged 65-74 and 75 and more years showed the significantly higher prevalence of edentulousness and the lower mean count of remaining teeth in institutionalised seniors when compared with those living independently (age 65-74 - 50.1 % vs. 21.0 %, 4.16 % vs. 10.91 %, age 75 and more - 65.2 % vs. 51.7 %, 2.24 % vs. 5.06 %). Significantly lower count of institutionalised individuals had enough teeth present to evaluate their periodontal status but the prevalence of periodontal disease did not differ significantly between the groups of institutionalised and independently living seniors. Restoration of remaining teeth and prosthetic rehabilitation in institutionalised seniors were significantly worse when compared with independenty living individuals.